2011
DOI: 10.1055/s-0029-1245871
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Over the Scope Clips (OTSC) with an Nd:YAG Laser

Abstract: Until recently there has been no technique available which reproducibly and safely allows endoscopic closures of penetrating defects within the digestive tract. With the new "over the scope clipping system" (OTSC system), which regarding design and function is similar to a bear-trap, a method is available for the endoscopic closure of fistulas and perforations. The OTSC-systems are designed for permanent placement. However, in the case of misplacement or the need to remove the clip after healing of the defect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…Very recently, a technique to remove the OTSC by using an Nd:YAG laser was shown in 3 patients. 13 In this case study, clinically relevant thermal lesions were not observed after the procedure, and the OTSC could be always removed.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Very recently, a technique to remove the OTSC by using an Nd:YAG laser was shown in 3 patients. 13 In this case study, clinically relevant thermal lesions were not observed after the procedure, and the OTSC could be always removed.…”
Section: Discussionmentioning
confidence: 83%
“…In this scenario, the endoscopist might place the OTSC in the wrong position or the clip might be placed in a location that hampers additional endoscopic therapy, such as described in a case of cholangiocarcinoma where the OTSC inhibited treatment of the tumor by endoscopic photodynamic therapy. 13 In these circumstances, the OTSC may need to be removed. Thus, the availability of techniques to do so is important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in F2 Figure 2, there are 3 types of Ovesco OTSC: "atraumatic" (blunt teeth, primarily designed for hemostasis), traumatic (with short sharp teeth designed for defect closure), and "gastric closure" (with longer teeth designed for improved tissue grip for full-thickness closure and NOTES applications). Because of the strength of OTSCs, they may be difficult (though not impossible [10][11][12][13][14]) to remove once deployed.…”
Section: Ots Clipsmentioning
confidence: 99%
“…In this respect, although OTSC is reported to result in good clinical outcome following its use in endoscopic closure of perforations [18], additional cumbersome procedure is needed for clip removal; whilst TTSC may drop off following application [19].…”
Section: Introductionmentioning
confidence: 99%